Effect of Er: YAG Laser Irradiation on Bone Metabolism-Related Factors Using Cultured Human Osteoblasts: Examination of the effect of Er: YAG laser irradiation using osteoblasts - Yuji, Tsuka; Kunimatsu, Ryo; Gunji, Hidemi; Sakata, Shuzo; Nakatani, Ayaka; Oshima, Sho; Rikitake, Kodai; Nurul Aisyah, Purtranti; Kado, Isamu; Tanimoto, Kotaro (Journal of Lasers in Medical Sciences, 2023)
Introduction: A variety of laser treatments have been applied in numerous medical fields. In dentistry, laser treatments are used for caries, root canals, and periodontal disease, as well as surgical resection. Numerous reports have recently been published on the use of lasers for bone regeneration. If laser irradiation is found to promote the activation of bone metabolism, it might also be effective for periodontal treatment, peri implantitis, and bone regeneration. Therefore, the present in vitro study aimed to elucidate the mechanisms underlying the effects of erbium-doped yttrium aluminum garnet (Er: YAG) laser irradiation on the bone using osteoblast-like cells. Methods: Osteoblast-like Saos 2 cells (5.0×104 cells) were seeded in 24-well plates. 24 hours after being seeded, the cells were subjected to 0.3 W, 0.6 W, and 2.0 W Er: YAG laser irradiation and then allowed to recover for 48 hours. The expression levels of bone metabolism-related factors alkaline phosphatase (ALP), bone sialoprotein (BSP), and osteoprotegerin (OPG) were then evaluated using reverse transcription–quantitative polymerase chain reaction and western blot analyses. Results: Saos 2 cells subjected to Er: YAG laser irradiation at 0.3 W, 0.6 W, and 2.0 W showed normal growth. When the Er: YAG laser irradiation and control groups were compared after 48 hours, increases were observed in ALP, BSP, and OPG gene and protein expression in the 2.0 W group. Similar results were obtained in the western blot analysis. Conclusion: These findings suggest that the Er: YAG laser irradiation of osteoblast-like cells is effective for activating bone metabolism factors.